Analysis the Influence Entrepreneurship Knowledge, Circle of Friends and Economic Background on Students Interest to be Entrepreneur - Kusumaningrum, Martina; Nuryana, Ita (Universitas Muhammadiyah Surakarta, 2022)
This research aims to analyze the influence of Entrepreneurship Knowledge, Circle of Friends, and Economic Background on Students Interest in being entrepreneurs. This type of research is quantitative research as a research method and uses multiple regression analysis to analyze data. The subject of this research is students from the Faculty of Economics and Business at the Universitas Muhammadiyah Surakarta, with 120 students as samples. The technique for collecting data uses a questionnaire from google form. The result shows that the Circle of Friends (X2) and Economic Background (X3) have a positive effect on students' interest (Y). Still, Entrepreneurship Knowledge (X1) has not positively impacted Student Interest (Y).